In Vitro Evaluation of a Novel Computationally Designed Anticancer Peptide in Ovarian Cancer Cell Models - Shaala, Basma A (AUC Knowledge Fountain, 2025)
Ovarian cancer remains one of the leading causes of cancer-related mortality among women, highlighting the need for novel therapeutic agents with improved selectivity and reduced toxicity. Anticancer peptides (ACPs) have emerged as promising candidates due to their ability to selectively target cancer cells. In this study, the anticancer activity of a computationally designed ACP was evaluated in vitro using the SKOV-3 ovarian cancer cell line, with HEK cells employed as a non-cancerous control. Cell viability was assessed using the MTT assay, and cytotoxicity was further confirmed by the trypan blue exclusion method. Apoptosis and necrosis were analyzed using Annexin V-FITC/Propidium iodide staining. The effects of ACP treatment on cell migration and invasion were examined using wound-healing and Transwell invasion assays, respectively. Quantitative real-time PCR (qPCR) was performed to evaluate the expression of genes associated with apoptosis, proliferation, and epithelial–mesenchymal transition (EMT), with GAPDH used as a housekeeping gene. ACP treatment resulted in a dose-dependent reduction in SKOV-3 cell viability, while minimal cytotoxic effects were observed in HEK cells, indicating selective anticancer activity. Trypan blue analysis confirmed increased cell death following ACP treatment. Apoptosis analysis revealed a significant increase in early apoptotic cells in ACP-treated SKOV-3 cells compared with untreated controls. Functional assays demonstrated a marked inhibition of cell migration and invasion upon ACP treatment. Gene expression analysis showed modulation of apoptosis- and proliferation-associated markers; however, no statistically significant changes were observed in the EMT-related genes TWIST1 and N-cadherin. This study provides functional evidence that the computationally designed anticancer peptide (ACP) exhibits selective anticancer activity against ovarian cancer cells in vitro, associated with increased apoptosis and reduced migratory and invasive behaviors.